Prevalence of antibody to parvovirus B19 in an isolated community in the amazon region of Brazil - Mello, Wyller Alencar de (1989)
Ministério da Saúde. Fundação Serviços de Saúde Pública. Instituto Evandro Chagas. Belém, PA, Brasil.